Fulminant Nonocclusive Mesenteric Ischemia Just after Hip Arthroplasty - Maria Auxiliadora-Martins; Gil Cezar Alkmin-Teixeira; Omar Feres; Olindo Assis Martins-Filho; Anibal Basile-Filho (Case Reports in Medicine)
Nonocclusive mesenteric ischemia (NOMI) is not a rare clinical entity in intensive medicine, and it can be a consequence of several clinical or surgical situations. This pathology results from reduced intestinal microvascular blood supply associated with an acute inflammatory process, culminating with bowel necrosis. This is a case on a female patient who developed immediate postsurgical NOMI following hip arthroplasty and died. Since diagnosis of this potentially fatal condition remains a dilemma, NOMI should always be considered an eventual postoperative complication in high-risk surgical patients such as elderly individuals with previous history of nicotine abuse, congestive heart failure, and essential hypertension. The present paper highlights the importance of early diagnosis and prompt adequate treatment of NOMI in subjects with diminished cardiac output and severe abdominal pain.